Aktywizowanie uczniów w poszerzonym środowisku uczenia się - możliwości wykorzystania forum dyskusyjnego = Activating students in extended learning environment - possibilities of using a discussion forum - Sajdak, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the possibilities of using information and communication technologies in the teaching process on the example of moderating a discussion forum on an e-learning platform. The author, using her own experience and a phenomenological insight into her own practice, gives practical tips on how to activate persons learning by conducting a discussion in virtual space.
Keywords: uczenie się; e-learning; forum dyskusyjne; learning; discussion forums